Pengaruh Karir Potensial dan Motivasi Terhadap Performa Kerja: Studi pada Pelaut yang Bekerja pada Perusahaan Penyedia Awak Kapal Tahun 2023 - Widanto M. Adi; Fitri Suprapti; Retno Anggoro; Lia R. Asfirah (SAINTARA, 2023)
This study aims to examine the influence of career potential and motivation on performa kerja within ship manning agencies. Ship manning agencies play a crucial role in the maritime industry by providing crew members for vessels. Understanding the factors that contribute to enhanced performa kerja in this sector is vital for the efficiency and effectiveness of these agencies. The research problem revolves around identifying the extent to which career potential and motivation affect performa kerja among employees in ship manning agencies. Additionally, the study aims to explore the specific dimensions of career potential and motivation that have the most significant impact on performa kerja. To solve the research problem, a quantitative research approach will be employed. A survey questionnaire will be distributed among employees of various ship manning agencies, collecting data on career potential, motivation, and performa kerja. Statistical analysis, such as correlation and regression analysis, will be conducted to examine the relationships between the variables. Results of data processing and tests between variables using SPSS and SEM AMOS series 24 applications. The results of the construct variable tests showed that all constructs met the eligibility standards and the results obtained were that career potential had an effect on work performance of 0.893, the effect of motivation on work performance was 0.844. so that it meets the eligibility standard for Correlation > rtable, namely 0.3494. The results of the Amos SEM test show that all variable test results (estimated regression weights) are ≤ 1.96 so that the regression test results of all variables and indicators in this study are significant. The sample used in this research was sailors who attached ships to crew providing companies totaling 150 respondents. The objects of this research are two companies providing crew vessels in Jakarta, namely PT. Oceanindo Ship Crew Staffing Agent, PT. Scorpa Pranedya Utama.